In Vitro and In Vivo Study of Poly(ethylene glycol) Conjugated Ibuprofen to Extend the Duration of Action - Nayak, Anjali (Österreichische Apotheker-Verlagsgesellschaft, 2011)
Ibuprofen–polyethylene glycol (PEG) conjugates (PEG-Ibu) were prepared and their potential as a prolonged release system was investigated. Two PEG-Ibu conjugates were synthesized from Ibuprofen and PEG with two different molecular weights by esterification in the presence of DCC and DMAP. The PEG-Ibu conjugates were characterized by FT-IR, (1)H NMR, Mass spectroscopy and DSC analysis. The solubility study in aqueous system showed an increase in solubility of conjugates. The dissolution / hydrolysis studies showed a specific acid–base catalysis pattern dependent on the pH of the medium. This indicated a good chemical stability in aqueous buffer solution of acidic medium and the extended release behavior was found in both prodrugs after 9 hour. The results demonstrate that, in the same condition, the rate of hydrolysis for PEG(4000)-Ibu is slower than other. The Writhing induced by acetic acid experiment and paw edema test after oral administration showed that both conjugates had extended analgesic and anti-inflammatory effects compared with Ibuprofen. These results suggest that PEG-Ibu could be a promising NSAID prodrug with an extended pharmacological effect owing to delayed-release of parent drug.